2014
DOI: 10.1900/rds.2014.11.245
|View full text |Cite
|
Sign up to set email alerts
|

Ancient Wheat Diet Delays Diabetes Development in a Type 2 Diabetes Animal Model

Abstract: ■ Abstract AIM:The main objective was to investigate the physiological effects of ancient wheat whole grain flour diets on the development and progression of type 2 diabetes in Zucker diabetic fatty rats, and specifically to look at the acute glycemic responses. METHODS: An intervention study was conducted, involving 40 ZDF rats consuming one of 5 different diets (emmer, einkorn, spelt, rye and refined wheat) for 9 weeks. Refined wheat flour and whole grain rye flour were included as negative and positive cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Epidemiological studies have shown a beneficial effect of cereal fiber, especially wheat fiber, in reducing the risk of diabetes . Ancient WG wheat diets delayed diabetes development in a T2D animal model . Diets containing 5% WB could decrease fasting blood sugar by ∼20% in diabetic rats .…”
Section: Health‐promoting Effects Of Wheat Phytochemicalsmentioning
confidence: 99%
“…Epidemiological studies have shown a beneficial effect of cereal fiber, especially wheat fiber, in reducing the risk of diabetes . Ancient WG wheat diets delayed diabetes development in a T2D animal model . Diets containing 5% WB could decrease fasting blood sugar by ∼20% in diabetic rats .…”
Section: Health‐promoting Effects Of Wheat Phytochemicalsmentioning
confidence: 99%
“…The effects of whole grain flour obtained from modern and ancient (spelt, emmer, and einkorn) wheats on the development and course of diabetes in the Zucker diabetic fatty (ZDF) rats were assessed (Thorup and others ). Results showed that the disorder was less pronounced with ancient grains fed to the ZDF rats than with the modern wheat; this was ascribed to a down‐regulation of the expression of important regulatory genes in the liver.…”
Section: Nutritional Qualities Of Modern and Ancient Wheatsmentioning
confidence: 99%
“…These beneficial properties are ascribed to higher levels of proteins, lipids (mostly unsaturated fatty acids), soluble fibers, minerals, vitamins and phytochemicals (Dinelli et al, 2007;Hidalgo & Brandolini, 2014;Piergiovanni, Rizzi, Pannacciulli, & Gatta, 1997;Vrček et al, 2014). They are chiefly concentrated in the outer layers of grains (Adom, Sorrells, & Liu, 2005;Landberg, Kamal-Eldin, Salmenkallio-Marttila, Rouau, & Åman, 2008), which could explain the reduction of the risk of developing many diseases that is associated with higher whole grain consumption (Poutanen et al, 2008;Thorup, Gregersen, & Jeppesen, 2014). Nowadays, the higher nutritional value of whole grains than refined grains is recognized (Slavin, 2003), while the nutritional dominance of ancient vs modern grains is still controversial.…”
Section: Introductionmentioning
confidence: 99%